1993
DOI: 10.1039/p29930001659
|View full text |Cite
|
Sign up to set email alerts
|

Dual reaction channels for solvolyses of acyl chlorides in alcohol–water mixtures

Abstract: Rate constants are reported for solvolyses at 0°C of trimethylacetyl chloride (3) in 90-30% V/V acetonitrile-, acetone-, ethanol-and methanol-water mixtures, of adamantane-1 -carbony1 chloride (4) in 90-60% acetone-, ethanol-and methanol-water mixtures, and of cyclopropanecarbonyl chloride (5) in 9040% acetone-water. Quantitative product data (acid and ester) are also reported for solvolyses of trimethylacetyl chloride in 98-20% ethanol-and methanol-water mixtures. Product selectivities (S) show maxima in 90-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Substrates of 3 and 5 were reported that they are mainly followed by unimolecular pathway (ionization) due to the resonance effect of paramethoxy substituent. [6][7][8][9]15 The l/m ratio of 1 in all range of solvents was 0.47, it is the similar value of 3 and 5, which means that the solvolysis reaction pathway of 1 containing para-methoxy substituent, is consistent with the results of 3 and 5. In case of 2, the l/m ratio was 2.59 in 17 nucleophilic solvents and was 0.64 in 8 electrophilic solvents, respectively.…”
supporting
confidence: 78%
“…Substrates of 3 and 5 were reported that they are mainly followed by unimolecular pathway (ionization) due to the resonance effect of paramethoxy substituent. [6][7][8][9]15 The l/m ratio of 1 in all range of solvents was 0.47, it is the similar value of 3 and 5, which means that the solvolysis reaction pathway of 1 containing para-methoxy substituent, is consistent with the results of 3 and 5. In case of 2, the l/m ratio was 2.59 in 17 nucleophilic solvents and was 0.64 in 8 electrophilic solvents, respectively.…”
supporting
confidence: 78%
“…S N 1 like pathways, with the dominance of ionization of chloride ion, were considered to occur for compounds bearing very strong e‐d groups in strongly polar protic solvents 17–19. Competing S N 2 and S N 1 mechanisms were proposed for hydrolyses with increasing contribution of the S N 1 pathway, when the water content of the solvent mixtures increased 12, 20–25. The mechanism of the hydrolyses of acid chlorides bearing strong e‐w groups was considered to change for an Ad‐E pathway with rate determining addition step 12, 16, 25–28.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bentley has made extensive use of this technique in establishing (or excluding) dual reaction channels in the solvolyses of acyl chlorides (RCOCl), and also sulfonyl chlorides (RSO 2 Cl), in alcohol-water mixtures. These solvolyses can lead to either an ester (attack by alcohol) or an acid (attack by water) [36,37,38,39]. …”
Section: Introductionmentioning
confidence: 99%